(untitled) (Constructionism Conference Proceedings, 2025)
Computing education often lacks real-world context, which can hinder young learners in connecting abstract concepts with nature experiences. The project “Digital Storytelling with Plants,” hosted at the Botanical Garden at the University of Zurich, integrates computing education with nature-based learning for children aged 8 to 15. Participants (105 in total) combined art, programming, and video production in workshops centered on plant life. The project assessed shifts in motivation for media and technology usage and interest in botany. Rooted in constructionist pedagogy, the workshops emphasized nature-based, hands-on, and student-centered learning. Findings show that narrative and reflection foster interest in both plants and technology, with measurable gains in awareness, motivation, and confidence, highlighting the value of digital tools in environmental education.